Prevalence of QTc prolongation among hypertensive patients and its association with other co-morbidities - Janakiraman, Sathiyanarayanan; Arivazhagan, Ramesh Bala; Chinnusamy, Manokaran (International Journal of Advances in Medicine, 2022)
Background: Hypertension, an iceberg disease contributes significantly to the global health burden. This pan-endemic disease is a harbinger for cardiovascular events, especially life-threatening arrhythmias. A simple and cost-effective electrocardiogram serves as an effective tool to identify and evaluate hypertensives with high cardiovascular risk. QTc interval which indicates repolarization abnormality is one such effective tool. The study aimed at describing the prevalence of QTc prolongation among hypertensive individuals and also to assess the association of QTc prolongation with various co-morbidities. Methods: One hundred and fifty-nine hypertensive patients were evaluated in this cross-sectional study for six months. Demographic variables, biochemical parameters, blood pressure and electrocardiogram were recorded for all the patients. Data obtained were statistically evaluated. Results: The mean age of participants was 55.6 years (SD±6.76). There were 103 males (64.4%) and 43 females (35.6%). QTc prolongation was noted in 52.5% of the population studied. Statistically significant QTc prolongation among poorly controlled hypertensive was 59% when compared to that of controlled hypertensive at 37.5% was noted. About 26% of the participants were smokers, 27% were alcoholics and 60% had co-existing diabetes mellitus. Diabetes and gender were found to have a statistically significant association with QTc prolongation. Conclusions: The study found a positive correlation between prolonged QTc and hypertensives and hypertensives with coexisting diabetes. To mitigate the consequences of hypertension, the study recommends early diagnosis, stringent blood pressure control, efficient and effective use of QTc measurement, and preventive pharmacotherapy.